Konsep Ekoteologi dalam Perspektif Emil Salim - Nurul Fitriyani; Uqbatul Khoir Rambe; Hotmatua Paralihan (LPPM IAIN Sorong, 2026)
The environmental crisis has become a global issue influenced not only by technical and economic factors but also by the way humans perceive and interact with nature. Development models that prioritize economic growth often neglect environmental carrying capacity, resulting in various ecological problems, including climate change, pollution, deforestation, and biodiversity loss. This study aims to analyze the concept of ecotheology from the perspective of Emil Salim's thought, explain the relationship between humans, nature, and development, and examine its relevance in addressing contemporary environmental crises. This research employs a qualitative method using a library research approach. The data were collected from Emil Salim's works, scholarly books, and relevant scientific journal articles and analyzed through content analysis to identify the relationship between Emil Salim's ideas on sustainable development and the principles of Islamic ecotheology. The findings reveal that although Emil Salim did not explicitly use the term ecotheology, his environmental thought is closely aligned with the Islamic principles of tawhid (divine unity), khalifah (stewardship), amanah (trust), and mizan (balance). The environment is viewed as an integrated system of life whose balance must be preserved, while development should be implemented sustainably by balancing economic, social, and ecological dimensions. Therefore, Emil Salim's perspective provides a significant contribution to the development of contextual Islamic ecotheological studies and offers an ethical foundation for strengthening ecological awareness and promoting environmental sustainability.